Analysis of the humoral and cell-mediated immune response in heterologous and homologous SARS-CoV-2 revaccination - O. M. Drapkina; M. G. Chashchin; S. A. Berns; A. Yu. Gorshkov; O. V. Zhdanova; L. N. Ryzhakova; O. A. Litinskaya (Кардиоваскулярная терапия и профилактика, 2023)
The effectiveness of humoral and cell-mediated immunity as a result of primary vaccination for Severe Acute Respiratory Syndrome- related CoronaVirus 2 (SARS-CoV-2), as well as the effectiveness of revaccination, is an important research problem. Studying and selecting optimal revaccination regimens will allow for long-term protection against coronavirus disease 2019 (COVID-19).Aim. To study the severity of humoral and cell-mediated immune response in various (homo- and heterologous) SARS-CoV-2 revaccination regimens as part of a prospective observational study 18 and 24 months after primary vaccination.Material and methods. The study was carried out within the prospective registry SATURN, which included individuals who received various SARS-CoV-2 revaccination (homo- and heterologous regimens) based on a combination of two following vaccines: Gam- COVID-Vac and CoviVac. Depending on the chosen regimen, 3 following groups were formed: group I (n=106) — participants with a homologous Gam- COVID-Vac regimen at each stage of vaccination and revaccination; group II (n=54) — participants with a heterologous regimen of sequential administration of Gam- COVID-Vac and CoviVac at the stage of vaccination and revaccination; group III (n=40) — participants with a homologous CoviVac regimen at the stage of vaccination and revaccination. At the first visit, all participants underwent a medical history collection, examination, and identification of potential contraindications to vaccination. At each subsequent visit, the level of anti- SARS-CoV-2 S-glycoprotein IgG antibodies was additionally determined. At visits 1, 3 and 5, the activity of specifically sensitized T-lymphocytes to the surface and nuclear antigen of SARS-CoV-2 was assessed. The IgG concentration was analyzed using the Abbott Architect SARS-CoV-2 IgG reagent kit, while T-cell immunity was assessed using the T-Spot.COVID test system (Oxford Immunotec). Visit 1 corresponded to the 1st stage of primary vaccination, visit 2 — 2nd stage of primary vaccination, visit 3 (12 months after visit 1) — 1st stage of revaccination, visit 3 (21 days after visit 3) — 2nd stage of revaccination, visit 5 –18 months after primary vaccination, visit 6 — 24 months after primary vaccination.Results. The average level of anti- SARS-CoV-2 S-glycoprotein IgG antibodies in group I at visit 3 was 520 [478; 540] BAU/ml, in group II — 499 [199,5; 540] BAU/ml and in group III — 456 [389; 509,5] BAU/ml. The values were comparable to those obtained at visit 6. However, in group II, IgG level at visit 5 was significantly higher compared to visit 6 (p=0,001). The greatest decrease by visit 5 in the number of active T cells responding to SARS-CoV-2 Spike stimulation was recorded in group III (5,00 [0,50; 11,50] vs 1,00 [0,00; 5,50]; relative changes -80,0%; p=0,067). Also, among patients in group III, there was a significant decrease in the number of active T cells responding to stimulation with SARS-CoV-2 nucleocapsid (10,00 [3,00; 22,50] vs 1,00 [0,00; 11,50]; relative changes -90,0%; p=0,0160). Participants in groups I and II demonstrated stable results on visit 5, relative to visit 3. In all studied groups, no significant relationship was found between IgG levels to SARS-CoV-2 S-glycopeptide and the number of active T cells. Strong positive relationships were found between the level of active T cells responding to SARS-CoV-2 spike stimulation and the level of active T cells responding to SARS-CoV-2 nucleocapsid stimulation: group I (ρ=0,807; p<0,001), group II (ρ=0,748; p<0,001) and group III (ρ=0,902; p<0,001).Conclusion. The use of homologous and heterologous SARS-CoV-2 vaccination demonstrates relatively stable level of both humoral and cell-mediated 18 and 24 months after the first stage of vaccination. Revaccination with a homologous regimen (CoviVac at both stages) ensured stable level of anti- SARS-CoV-2 S-glycopeptide IgG antibodies. However, this regimen was characterized by a significant decrease in the long-term period in the number of active T cells responding to stimulation of SARS-CoV-2 surface and nuclear antigen.